A data association algorithm based on the minimal angular distance sum for angle‐only measurements with the sensor position unknown - Ma, Feng; Lu, Huanzhang; Shen, Xinglin (IET radar, sonar & navigation, 2025)
Data association technology can determine the corresponding relationships between target data (measurements or tracks) on different platforms, laying the foundation for target allocation and collaborative strikes. For targets with smaller volumes and similar appearances, such as drone swarms and warhead swarms, angle measurement provides important information for the use of passive optical sensors to associate target data. The classic data association technology for angle‐only measurement relies on precise knowledge of the sensor position, hindering their application to drone swarms or other low‐cost mobile platforms. This paper proposes a data association algorithm based on the minimum angular distance sum, whose calculation process does not involve the sensor position information, making angle‐only measurement data association technology independent of the sensor position information. Both the simulation results and the experimental results validated the effectiveness of the proposed algorithm.